HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN PEMBERIAN MP-ASI PADA BAYI USIA 6-12 BULAN DI WILAYAH KERJA UPTD PUSKESMAS SIMEULUE BARAT TAHUN 2024 - Radia, Hikma; T. Alamsyah (Jurnal Biogenerasi, 2025)
Complementary Feeding (MP-ASI) plays a vital role for infants aged 6–12 months in fulfilling nutritional needs that can no longer be met by breast milk alone. Proper MP-ASI provision is crucial in supporting optimal growth and development during this critical period. Maternal knowledge and attitudes are two key factors influencing the success of complementary feeding practices. This study aims to examine the relationship between maternal knowledge and attitudes and the practice of MP-ASI provision in the working area of UPTD Puskesmas Simeulue Barat in 2024. A quantitative, cross-sectional design was employed, involving 49 mothers with infants aged 6–12 months, selected through total sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square test. The results revealed a significant relationship between maternal knowledge (p = 0.040) and attitudes (p = 0.017) and MP-ASI feeding practices. It is recommended that the local health center strengthen education efforts at community health posts (posyandu) regarding the appropriate timing, frequency, and texture of MP-ASI, supported by health cadres and interactive visual media. In addition, practical training for mothers on preparing nutritious MP-ASI using local ingredients should be encouraged. Future research is suggested to include additional variables such as cultural influences, family and social support, and access to information.